Role of Private Sector in Developing Employment through Skill Development Programme: A Case Study of Odisha (International Journal of Scientific Research and Management (IJSRM), 2021)
तत्कर्म यन्न बन्धाय सा विद्या या विमुक्तये । आयासायापरं कर्म विद्यान्या शिल्पनैपुणम् ॥ The above mentioned slokas are derived from VISHNU PURANA a great mythological and is one of the eighteen Mahapuranas, a genre of ancient and medieval texts of Hinduism. It means Action is that, which does not promote attachment; that is knowledge which liberates. All other action is mere effort/hardship; all other knowledge is merely another skill/craftsmanship. Present day skill refers to knowledge which can be applied in executing/solving a particular task. This also provides a person to earn his day to day livelihoods’. The skill development programme initiated at different level such as local bodies, corporatehouses, state government, central government and other authorities has the objective to empower the unemployed youth to increase their employability or engagement opportunities, so that they can be useful in contributing their individual income as well as in the national income. The corporate houses have launched massive skill development programmes through their CSR spending. They ensure to train and develop skill at the ground level and facilitate in the employment/engagement after successful completion of training. The present research paper is undertaken to study how the corporate houses impacting skill development programme in the society through their CSR programmes.